Awakening the Spirit of Volunteerism in Buea Subdivision a A Case Study of the Catholic University Institute of Buea- The Entrepreneural University (Global Journal of Management and Business Research, 2016)
Volunteerism is the principle of donating time and energy for the benefit of other people in the community as a social responsibility rather than for any financial reward It is intended to develop your skills and also it promote goodness or to improve human quality of life It has a positive benefit or impact for the volunteer as well as for the person or community served The Catholic University Institute of Buea through its various schools and the college of business and technology offers service-learning which allow the students to serve a group through volunteering while earning education credits This the authorities of the Catholic University Institute of Buea sees it as a powerful means of preparing students to become more caring and responsible citizens thus helping the university to make good on their pledge to serve the society or community and also as a good positional tool It engages both the mind and the heart hence it provide a powerful learning experience by so doing volunteerism thus captures students interest
Keywords: technology offers service-learning